EDMD-Causing Emerin Mutant Myogenic Progenitors Exhibit Impaired Differentiation Using Similar Mechanisms - Ashvin Iyer; James M. Holaska (Cells, 2020)
Mutations in the gene encoding emerin (EMD) cause Emery–Dreifuss muscular dystrophy (EDMD1), an inherited disorder characterized by progressive skeletal muscle wasting, irregular heart rhythms and contractures of major tendons. The skeletal muscle defects seen in EDMD are caused by failure of muscle stem cells to differentiate and regenerate the damaged muscle. However, the underlying mechanisms remain poorly understood. Most EDMD1 patients harbor nonsense mutations and have no detectable emerin protein. There are three EDMD-causing emerin mutants (S54F, Q133H, and Δ95–99) that localize correctly to the nuclear envelope and are expressed at wildtype levels. We hypothesized these emerin mutants would share in the disruption of key molecular pathways involved in myogenic differentiation. We generated myogenic progenitors expressing wildtype emerin and each EDMD1-causing emerin mutation (S54F, Q133H, Δ95–99) in an emerin-null (EMD−/y) background. S54F, Q133H, and Δ95–99 failed to rescue EMD−/y myogenic differentiation, while wildtype emerin efficiently rescued differentiation. RNA sequencing was done to identify pathways and networks important for emerin regulation of myogenic differentiation. This analysis significantly reduced the number of pathways implicated in EDMD1 muscle pathogenesis.